(untitled) (Zaporizhzhia Historical Review, 2021)
The author compares teaching to the fighting of the spear of the Ukrainian cavalry in 1922 and martial art of the Cossackís (at the beginning of XX century). The comparative analysis shows that a Cossacks art was more accomplished.